Seleção em coentro (Coriandrum sativum L.) para resistência à vespa do fruto. - Silva, Maria Stela Bezerra da (1996)
This work was conducted at the "Departamento de Fitotecnia da Universidade Federal do Ceará, Brasil". The objective of this research study was to testify the possibility of coriander breeding program, to obtain a material resistant the crosspath, as well as to evaluate the variables more adequate. Randornized blocks design were used with three replications. Ten generation/genotypes represented the treatments. During S6 and S7 generations, purpure of this analyze, three variables were evaluated: 1) useful leaves 30 days after; 2) total umbels quantity and 3) attacked fruits percentage by the crosspath. Data show that is possible a coriander breeding program. Results show too that the decrease of attacked fruits percentage by the crosspath is possible through of minor total umbels quantity or major fruit weight, fruits quantity, number of days for leaves system change, number primaries branchs and major leaves quantity